Ecological parasitology reflections on 50 years of research in aquatic ecosystems - Esch, Gerald W.; Allen, Charles M. (Chichester, West Sussex , UK John Wiley & Sons, 2016)
Professor Gerald Esch has already published two books in what is becoming an informal series of essays exploring the way that discoveries about the biology of parasites have influenced ecological and evolutionary theories over a career that has spanned nearly 50 years. This book will be the third set of essays and will focus on key moments of discovery and explore how these achievements were due to collaboration, mentoring, and community building within the field of ecological parasitology. The book will not only describe case studies, pure science and biology but also act as a career guide for early-career ecologists emphasizing the importance of collaboration in the advancement of science.--Provided by publisher.
1. The beginning -- 2. The end of the beginning -- 3. Gull Lake and the W.K. Kellogg Biological Station -- 4. Gull Lake and the connection with the Savannah River Ecology Laboratory -- 5. Development of some conceptual notions -- 6. The pond. Part I -- 7. The pond. Part II -- 8. The big lake -- 9. The strigeids -- 10. Some small streams and small ponds -- 11. Red sore disease -- 12. The end, almost -- 13. The catastrophic collapse of the larval trematode component community in Charlie's Pond (North Carolina) -- 14. An epilogue: What's involved with graduate school?
Includes bibliographical references.
Keywords: Parasitology -- Environmental aspects; Aquatic habitats; Habitat (Ecology)